Health promotion: approaches to dietary salt reduction - Mushoriwa, Fadzai (Rhodes University, Faculty of Pharmacy, Pharmacy, 2017)
Background Globally, non-communicable diseases are the leading causes of mortality and morbidity, with the majority of these occurring in low-middle income countries. The devastating consequences of non-communicable diseases could be curtailed through better management of four modifiable factors: physical inactivity; tobacco use; harmful use of alcohol; and unhealthy diets. The World Health Organisation has recommended dietary salt reduction as a cost-effective strategy in combatting the burden of NCDs. Consumer awareness and education is one of three primary strategies that have been identified by the World Health Organisation to achieve population-wide salt reduction. It involves the provision of salt reduction knowledge and the promotion of healthy salt related practices. These campaigns are a necessity in populations with high discretionary salt use such as South Africa. For these health promotion activities to succeed, they need to be developed with consideration of factors such as the environment, culture, and socio-economic standing of the intended target population. This two-phase health promotion study was conducted at St Mary's Development and Care Centre and the Assumption Sisters Nutrition Centre. These are two community based organisations located in Grahamstown, South Africa. A needs assessment was conducted to identify the knowledge and practices of cooks and guardians from these centres on dietary salt reduction. The aim of the second phase of the study was to conduct an educational intervention and to develop a culturally appropriate and contextually specific health information intervention through a participatory process. Method: This was a qualitative study that was supported by elements of quantitative research.. The first phase of the current study was a needs assessment. The first step involved an observational phase with cooks from the centres. The aim was to observe their discretionary salt use during food preparation and to document the salt content in the processed foods available at each centre. Semi-structured interviews were then conducted, with 3 cooks and 16 guardians1 from the centres, to assess their knowledge and practices regarding salt reduction.Parents or the people responsible for the care of the children attending both centres. Guided by findings from the needs assessment phase, an educational intervention was developed. This phase involved the participatory development of three health information leaflets and a series of educational interactive sessions were conducted. Quantitative tests to assess the readability, suitability, and actionability were conducted on the leaflets. Qualitative assessment of the leaflets involved formative evaluations conducted by health care professionals, phase 1 participants, Rhodes University peer educators, an African languages and cultural expert, and a Rhodes University student wellness manager. This step was included to assess the content validity, context specificity, acceptability, and cultural appropriateness of the materials. Educational interactive sessions were guided by constructs of the Social Cognitive Theory and were conducted on three main topics: 'Salt and my health', 'Reducing salt in my diet', and 'Reading food labels'. Results: The majority of the processed foods available at both centres contained low to medium levels of salt. Children at the centres were not provided with salt shakers on the tables during meal times. Cooks did not use measuring utensils when adding salt during meal preparation. Semistructured interviews revealed that participants lacked both declarative and procedural knowledge. In terms of declarative knowledge, they were unaware of the daily salt intake recommendations and the relationship between salt and sodium. Participants were able to identify hypertension as one of the health related consequences of high salt consumption. Most participants were responsible for purchasing groceries in their households. Their selfreported food label reading behaviours and inability to read food labels highlighted their lack of procedural knowledge. Most participants reported that they added salt during meal preparation and at mealtimes, highlighting high discretionary salt use. Some participants were also aware of cultural or religious uses of salt. The developed health information leaflets were considered to be written at a readability level appropriate for the target audience. The leaflets were also deemed to be actionable, culturally appropriate, and contextually specific and suitable materials. The educational interactive sessions were found to be interesting and informative. Conclusions: Findings from the needs assessment revealed the need for an educational intervention to address the identified gaps in the participants' knowledge and practices regarding dietary salt reduction. The developed health information leaflets were found to be informative, culturally appropriate, and contextually specific, as planned. Interactive sessions provided an excellent platform to supply participants with concise and accurate information, increasing the possibility of improving their salt reduction related knowledge.
Keywords: Uncatalogued